(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article are considered problems to evolutions to migration of the population after decay USSR. It Is Analyzed factors, influencing upon moving the people, problems populations from Kyrgyzstana, questions entry and exit in own country. Keywords: state, migration, population, market economy.